1971
DOI: 10.1042/bj1210327
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the porphobilinogen deaminase–uroporphyrinogen cosynthetase system of cultured soya-bean cells

Abstract: 1. Porphobilinogenase was isolated and purified from soya-bean callus tissue; its components, porphobilinogen deaminase and uroporphyrinogen isomerase, were separated and purified. 2. The purified porphobilinogenase was resolved into two bands on starch-gel electrophoresis. The molecular weights of porphobilinogenase, deaminase and isomerase fractions were determined by the gel-filtration method. Porphobilinogenase activity was affected by the presence of air; uroporphyrinogens were only formed under anaerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1971
1971
1994
1994

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The uroporphyrinogen formed during the lag phase accounted for only part of the porphobilinogen consumed. The authors concluded that a pre cursor of uroporphyrinogen must have accumulated during the lag phase (95,96). They looked for such an intermediate in the incubation mixture and detected a uv absorbing species similar in its absorption properties to monopyrroles.…”
Section: Biosynthesis Of Uroporphyrinogen IIImentioning
confidence: 95%
See 1 more Smart Citation
“…The uroporphyrinogen formed during the lag phase accounted for only part of the porphobilinogen consumed. The authors concluded that a pre cursor of uroporphyrinogen must have accumulated during the lag phase (95,96). They looked for such an intermediate in the incubation mixture and detected a uv absorbing species similar in its absorption properties to monopyrroles.…”
Section: Biosynthesis Of Uroporphyrinogen IIImentioning
confidence: 95%
“…It is compat ible, however, with the presence of two substrate binding sites on the porpho bilinogenase. Ammonium ions appear to act competitively at the first binding site (96). From (13) and Cornford's (20) hypotheses.…”
Section: Biosynthesis Of Uroporphyrinogen IIImentioning
confidence: 96%
“…Ethionine is known to inhibit Chl synthesis in cultured soybean cells (13), presumably by antagonizing the methylation of Mg protoporphyrin by S-adenosylmethionine. However, in other organisms ethionine is known to act in one or more of several different ways (1), and resistant mutants are known to use various counteracting mechanisms, of which overproduction of methionine is but one (11).…”
Section: Resultsmentioning
confidence: 99%
“…The precise source of succinyl coenzyme A used for ALA synthesis is unknown and there may well be a separate pool of this compound not directly formed via the Kreb's cycle. Secondly, the mechanism of formation of uroporphyrinogens I and III from porphobilinogen remains obscure although numerous theories have been proposed (Llambias and Batlle, 1970). There is need for this to be established as there are almost certainly enzymic deficiencies of this pathway other than that of uroporphyrinogen III co-synthetase in congenital erythropoietic porphyria.…”
mentioning
confidence: 99%